Relationship between Helicobacter pylori Infection and Plasmacytoid and Myeloid Dendritic Cells in Peripheral Blood and Gastric Mucosa of Children - Anna Helmin-Basa; Małgorzata Wiese-Szadkowska; Anna Szaflarska-Popławska; Maciej Kłosowski; Milena Januszewska; Magdalena Bodnar; Andrzej Marszałek; Lidia Gackowska; Jacek Michalkiewicz (Mediators of Inflammation)
Purpose. To investigate the frequency and activation status of peripheral plasmacytoid DCs (pDCs) and myeloid DCs (mDCs) as well as gastric mucosa DC subset distribution in Helicobacter pylori- (H. pylori-) infected and noninfected children. Materials and Methods. Thirty-six children were studied; twenty-one had H. pylori. The frequencies of circulating pDCs (lineage-HLA-DR+CD123+) and mDCs (lineage-HLA-DR+CD11c+) and their activation status (CD83, CD86, and HLA-DR expression) were assessed by flow cytometry. Additionally, the densities of CD11c+, CD123+, CD83+, CD86+, and LAMP3+ cells in the gastric mucosa were determined by immunohistochemistry. Results. The frequency of circulating CD83+ mDCs was higher in H. pylori-infected children than in the noninfected controls. The pDCs demonstrated upregulated HLA-DR surface expression, but no change in CD86 expression. Additionally, the densities of gastric lamina propria CD11c+ cells and epithelial pDCs were increased. There was a significant association between frequency of circulating CD83+ mDCs and gastric lamina propria mDC infiltration. Conclusion. This study shows that although H. pylori-infected children had an increased population of mature mDCs bearing CD83 in the peripheral blood, they lack mature CD83+ mDCs in the gastric mucosa, which may promote tolerance to local antigens rather than immunity. In addition, this may reduce excessive inflammatory activity as reported for children compared to adults.